Inflation, exchange rate, and stock return: The evidence from the LQ45 index constituents in Indonesia - Martalena Martalena; Dini Iskandar; Bram Hadianto (Politeknik Ganesha Medan, 2023)
Economic factors affect companies, especially those listed in the capital market. Consequently, it fundamentally affects investors’ wealth, reflected by the stock price movement. Accordingly, this study aims to investigate and analyze the influence of inflation and exchange rate as related ones on stock return. The population comes from 20 coherent non-financial companies selected as LQ45 index from 2016 to 2022. Then, this study applies the Slovin formula with a 10% error margin to determine the sample size of 17, taken by a simple random sampling method. Also, it uses the regression model with pooling data and t-statistic to examine stock return determinants. Once meeting classical assumptions, this study checks the relationships. Its result demonstrates a positive influence of inflation on stock return, confirming the perspective declaring common stock becomes the hedging tool on inflation. Meanwhile, the IDR/USD exchange rate negatively associates with this return: The more powerful the US Dollar, the more diminished the stock price of non-financial companies belonging to the LQ45 index.